Verklarende Afrikaanse woordeboek8 as spieël van normverplasing - Carstens, Adelia (Lexikos, 1994)
Verklarende Afrikaanse woordeboek8 as a Reflector of Norm ReplacementNorm replacement is seen as a process whereby a norm or a set of norms are gradually replaced by another norm or set of norms. Over a period --- even a decade --- norm shifts of diverse types occur and are manifested in scientific, social and linguistic behaviour. The standard synchronic dictionaries of a language should reflect norm replacements, especially if these replacements have been lexicalised. VAW8 is reviewed with special regard to its reflection of ideological norm replacement, metalexicographical norm replacement and prescriptive norm replacement. The compilers are praised for their sensitive treatment of ideologically sensitive lexical items, i.a. by removing offensive racist terms and by sensitively redefining lemmas pertaining to certain race groups. They are also lauded for relaxing prescriptiveness regarding English loan words and Afrikaans colloquialisms. VAW8 is however criticised for its disregard of important metalexicographical developments of the past decade. It is argued that the implementation of theoretical insights could have contributed towards improved systematicity and user-friendliness as well as towards quicker information retrieval. Keywords: college dictionary, collocation, definition, encyclopedic, folk taxonomy, ideology, label, lexicographic theory, multilexical lemma, norm change, norm replacement, norm shift, prescriptiveness, racism, semantic shift, sexism, specificity, standard descriptive dictionary, sublexical lemma, verklarende afrikaanse woordeboek